Fabrication, Mechanical and Wear Properties of Aluminum (Al6061)-Silicon Carbide-Graphite Hybrid Metal Matrix Composites (Fracture and Structural Integrity, 2022)
In recent times, the use of aluminum alloy-based Hybrid Metal Matrix Composites (HMMCs) is being increased in aerospace and automotive applications. HMMCs compensate for the low desirable properties of each filler used. However, the mechanical properties of HMMCs are not well understood. In particular, microstructural investigations and wear optimization studies of HMMCs are not clear. Therefore, further studies are required. The present study is aimed at fabricating and mechanical and wear characterizing and microstructure investigating of Silicon Carbide (SiC) and Graphite (Gr) added in Aluminum (Al) alloy Al6061 HMMCs. The addition of SiC particles was in the range from 0 to 9 weight percentage (wt.%) in steps of 3, along with the addition of 1 wt.% Gr in powder form. The presence of alloying elements in the Al6061 alloy was identified using the Energy Dispersive X-Ray Analysis (EDX). The dispersion of SiC and Gr particles in the alloy was investigated using metallurgical microscope and Scanning Electron Microscopy (SEM). The gain in strength can be attributed to the growth in dislocation density. The nature of fracture was quasi-cleavage. The microstructure examination reveals the uniform dispersion of the reinforcement. Density, hardness, and Ultimate Tensile Strength values observed to be increased with increased contents of SiC reinforcement. Besides, wear studies were performed in dry sliding conditions. Optimization studies were performed to investigate the effect of parameters that affecting the wear. The sliding wear resistance was noticed to be improved concerning higher amounts of reinforcement leading to a decrease in delamination and adhesive wear. The predicted values for the wear rate have also been compared with the experimental results and good correlation is obtained.
Keywords: HMMCs; SEM; Ultimate tensile strength; Dislocation density; Siding wear; Optimization